If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(2+6k)=-6(-7k-3)
We simplify the equation to the form, which is simple to understand
6(2+6k)=-6(-7k-3)
Reorder the terms in parentheses
+(+12+36k)=-6*(-7k-3)
Remove unnecessary parentheses
+12+36k=-6+*(-7k-3+)
Reorder the terms in parentheses
+12+36k=+(+42k+18)
Remove unnecessary parentheses
+12+36k=+42k+18
We move all terms containing k to the left and all other terms to the right.
+36k-42k=+18-12
We simplify left and right side of the equation.
-6k=+6
We divide both sides of the equation by -6 to get k.
k=-1
| -(5x-1)+(2x+3)=17-(10x+1)+(x+6) | | 5*(x+3)-11=2x+19 | | x+38=2x+1 | | x^2-x-9xi-56-63i= | | f(5)=5-5 | | 17f+2=4f | | .5(8a+12)-27=15 | | p/8-1=7p/6+2 | | 40-2x=130-22x | | -3b+5b=2(2-b)+6(b-2) | | 4w+8=88 | | +2=7 | | (9x^4-6x^2+1)-(x^4-12x^3+34x^2+12x+1)=0 | | 2660+x(175.75)=5999.25 | | 72-x=86-2x | | -9+-5+14+-6= | | 5q+8=11 | | 2(3x+4y)=4x+2y | | 180-36-x=102 | | (13x-1)= | | 6+-4+-9+7= | | 0-8b=12 | | 4w+5z=6 | | 10x-1=1-4x | | 6y=5x+3 | | 3b+5b=2(2-b)+6(b-2) | | 3x-24=2x+35 | | 1.4x-0.9=33 | | (10x+29)= | | 5(y+4)=-8y-45 | | 6+2=14-x | | 315+15p=450 |